2008
DOI: 10.1002/bjs.5931
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms for the surgical management of retrorectal tumours

Abstract: A successful multidisciplinary surgical strategy, based on preoperative localization by MRI, has been developed for the treatment of retrorectal tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
134
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(144 citation statements)
references
References 27 publications
6
134
0
4
Order By: Relevance
“…These indications are known as ''atypical,'' as they do not involve the excision of rectal adenoma or carcinoma [33]. The atypical indications in our study is comparable to others reported that describes the indications in pelvic abscess, benign rectal stenosis, gastrointestinal stromal tumor, rectal prolapse, extraction of impacted fecaloma at the rectosigmoid junction and presacral tumor [34][35][36][37][38]. In recent years, TEM via natural orifices (natural orifice transluminal endoscopic surgery: NOTES) has been used to gain access to the peritoneal cavity and to perform intraabdominal procedures [39][40][41].…”
Section: Discussionsupporting
confidence: 84%
“…These indications are known as ''atypical,'' as they do not involve the excision of rectal adenoma or carcinoma [33]. The atypical indications in our study is comparable to others reported that describes the indications in pelvic abscess, benign rectal stenosis, gastrointestinal stromal tumor, rectal prolapse, extraction of impacted fecaloma at the rectosigmoid junction and presacral tumor [34][35][36][37][38]. In recent years, TEM via natural orifices (natural orifice transluminal endoscopic surgery: NOTES) has been used to gain access to the peritoneal cavity and to perform intraabdominal procedures [39][40][41].…”
Section: Discussionsupporting
confidence: 84%
“…Congenital masses are most common (66%). They are usually asymptomatic or present with nonspecific manifestations; furthermore, their location in a difficult-to-access anatomical region requires expertise regarding their diagnostic-therapeutic approach in order to deliver appropriate treatment (2). Their clinical presentation results from their mass effect, superinfection (in cystic growths), or organ invasion (in malignancies) (3), with pain being the most common symptom.…”
Section: Discussionmentioning
confidence: 99%
“…They are classified as epidermoid cysts, dermoid cysts, enteric cysts (tailgut cysts or hamartomas and cystic rectal duplication), and neuroenteric cysts, according to their origin and histopathologic features [5][6] . The diagnosis of retro rectal cysts can be accomplished with greater than 90% accuracy with computed tomography (CT) and magnetic resonance imaging (MRI) if the rectum is contrasted [3][4][5][6] . Such lesions warrant surgical excision to establish the diagnosis and to avoid complications.…”
Section: Discussionmentioning
confidence: 99%
“…Such lesions warrant surgical excision to establish the diagnosis and to avoid complications. MRI has been suggested to increase the accuracy of preoperative localization and to enable surgical planning 6 . Tran's rectal ultrasound, if available, can also be useful in defining the depth of infiltration in cases of rectal involvement 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation